Cutting across the century: an investigation of the close up and the long-shot in “cine choreography” since the invention of the camera - Pendlebury, Katy (The International Journal of Screendance, 2014)
The close-up has preoccupied practitioners and thinkers since the camera was invented. Later philosophers and historians such as Gilles Deleuze, Mary Ann Doane, and Erin Brannigan have revisited and reflected on the work of earlier theorists and filmmakers who wrote about the close-up, such as Bela Balázs, Walter Benjamin, and Jean Epstein. This essay endeavors to reflect on the genre of moving image practice, or “dancefilm,” using a variety of examples from different but related disciplines, and by analyzing these examples in relation to the wealth of thinking around the close‑up.